Evaluating the performance of a hybrid cooling and heating power system using Carbon dioxide energy storage. (November 2022) - Ramkumar, G.; Mulla, Najamussahar H.; Vibhakar, Chirag; Tamilselvi, M.; Boopathi, S.; Singh, Ngangbam Phalguni; Gomathi, S.; Mohanavel, V.; Sathyamurthy, Ravishankar
Abstract: Energy storing could correct an imbalance in the solar to electric power ratios among a Combined Heating, cooling and power system and its consumers, improving energy performance dramatically. Energy storage, on the other hand, adds to the complexities of the device's operational efficiency. While assessing the device's CO2 emissions in the operational state, the analysis comprises complete thermodynamics and thermo-economic evaluation. The effect of designing element modification on application functionality was examined next by varying the designed characteristics. Lastly, the proposed hybrid CCHP system is optimized for three objective operations: normalized exergy performance, CO2 emissions, and energy effectiveness. This paper presents a unique tri-generation method depending on the Trans-critical Brayton cycle and carbon dioxide energy storage (CO2 ES). The stored capacity has a minor impact on the framework's operating and cooling ranges, but the development in pressure change through the first throttle valve and temperature conditions broadens them. The capacity for heating and cooling rises in lockstep with stored pressures and falls in lock-step with differential pressure via the first throttle pressure regulator and ambient temperature. Moreover, the computational power is adequate for power system management. The proposed approach could also be used to optimize the functioning of a CCHP framework while taking into account demand-side responses.